Design a WEB-Based Stock Information System on PT. Giordano Indonesia Baywalk Mall Branch - Della Hetiosa; Ishak Kholil; Dicky Hariyanto (Universitas Islam Kuantan Singingi, 2022)
In today's age of globalization, information technology is advancing rapidly. In the case of computers, created to facilitate human work, the advances are both in the production of hardware and software. PT. Giordano Indonesia urgently needs an information system that can support its customers and provide them with satisfactory service. For this reason, the author is trying to create a final project about the goods transfer system on PT. Giordano Indonesia which has not been computerized yet. At this time PT. Giordano Indonesia is a company that operates in the retail sector. The existing system at PT. Giordano Indonesia is still operated manually, starting from data recording of goods to reporting, which includes the process of goods transfer, goods receipt data, goods issue data, storage of other data related to inventory, and report generation, which may cause errors in recording, inaccurate reports, and delays in finding the required data during the process. The development of this information system is the best solution to the problems that exist in this company and with a computerised system, effective and efficient activity can be achieved in supporting the activities in this company. The computerised system is better than the manual system to work more effectively and efficiently, and the current sales system is more conducive than the previous system.